Consistency in estimation and model selection of dynamic panel data models with fixed effects - Guangjie Li (Econometrics, 2015)
We examine the relationship between consistent parameter estimation and model selection for autoregressive panel data models with fixed effects. We find that the transformation of fixed effects proposed by Lancaster (2002) does not necessarily lead to consistent estimation of common parameters when some true exogenous regressors are excluded. We propose a data dependent way to specify the prior of the autoregressive coefficient and argue for comparing different model specifications before parameter estimation. Model selection properties of Bayes factors and Bayesian information criterion (BIC) are investigated. When model uncertainty is substantial, we recommend the use of Bayesian Model Averaging to obtain point estimators with lower root mean squared errors (RMSE). We also study the implications of different levels of inclusion probabilities by simulations.
Keywords: C52; C11; C13; C15; 330; dynamic panel data model with fixed effects; incidental parameter problem; consistency in estimation; model selection; bayesian model averaging